A Distributed Framework for High-Volume Time Series Data Imputation Using Ray and Cloud Infrastructure - Aayush Garg (International Journal of Intelligent Systems and Applications in Engineering, 2025)
The rapid growth of large-scale temporal data generated from healthcare systems, Internet of Things (IoT) devices, financial platforms, environmental monitoring systems, and smart infrastructures has increased the importance of efficient time series data management. However, missing values in high-volume time series datasets significantly affect the accuracy of predictive analytics, forecasting models, and real-time decision-making systems. Traditional centralized imputation techniques often face limitations related to scalability, computational overhead, and processing latency when dealing with massive datasets. This study proposes a distributed framework for high-volume time series data imputation using Ray and cloud infrastructure technologies. The framework integrates distributed task scheduling, parallel data processing, and machine learning-based imputation methods within a scalable cloud-enabled architecture. Multiple imputation techniques, including statistical methods and advanced machine learning models such as K-Nearest Neighbor (KNN), Random Forest, and Long Short-Term Memory (LSTM) networks, were evaluated under different missing data scenarios. The distributed framework demonstrated significant improvements in execution time, scalability, resource utilization, and fault tolerance compared to traditional centralized systems. Experimental findings further indicated that machine learning-based imputation models achieved higher predictive accuracy, with LSTM-based approaches producing the lowest error rates for sequential temporal datasets. Cloud-based deployment enabled dynamic resource allocation and efficient workload balancing during large-scale processing. The proposed framework offers an effective and scalable solution for real-time time series data imputation in modern big data environments and contributes to the advancement of distributed artificial intelligence and cloud-native analytics systems.